Transformasi Perpustakaan Berbasis Inklusi Sosial pada Dinas Perpustakaan dan Kearsipan Provinsi Kalimantan Barat - Yesika Eva Tania (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Social inclusion is a process of developing capacities for individuals and groups to participate in society. The purpose of this research was conducted to find out how the form of social inclusion-based library transformation activities, the supporting factors, and the constraints faced. This research uses a descriptive method with a qualitative approach. Methods of data collection in this study using observation, interviews, and documentary techniques. Data analysis techniques using data reduction, data presentation, and conclusions. Data validation techniques using increasing persistence, triangulation, holding member checks. The results showed that the Library and Archives Service of West Kalimantan Province held library activities based on social inclusion with two strategies, namely increasing information services and involving the community. Factors that support social inclusion-based library activities are budget, human resources and, following technological developments. The obstacles faced are the community and the budget.